Does green corporate investment really crowd out other business investment? - John P. Weche (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
Empirical studies on the link between green investment and other business investment at the firm level either focus on innovation specific types of investment or fail to consider the simultaneity of investment decisions. The analysis to be presented here offers a broad focus on different types of environmental protection investment and explicitly considers simultaneity issues, using newly created panel data for German manufacturing firms. Germany is an ideal case for testing the crowding-out hypothesis, due to its high level of environmental regulation and a significant presence of command-and-control style measures, which are especially under debate as a source of crowding-out. The estimation of a behavioral investment model supports a crowdingout of other business investment through environmental protection investment in general as well as its subcategories of add-on measures and investments in renewable energy. However, only the latter subcategory causes a crowding-out at the industry level.
Keywords: O32; O33; Q42; Q55; 330; green investment; business investment; renewable energy; crowding-out; manufacturing; Germany